ANALISIS KRITIK SASTRA DENGAN PENDEKATAN PRAGMATIK PADA KHUTBAH SYIQSYIQIYYAH KARYA SAYYIDINA ALI R.A. - Naja Alwi Mawardy; Ahmad Nurcholish (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2021)
This writing aims to analyze and interpret literary criticism with a pragmatic approach to Sayyidina Ali's sermon known as the "Syiqsyiqiyyah", so that it can be imitated by the current generation that a leader should have the values of tolerance, democracy, integrity, and solidarity. Especially in proving that the sermon has aesthetic values and benefits. The type of research used is library research using critical analysis method (critical analysis) with pragmatic descriptive approach. The result of the study prove that literary criticism of Sayyidina Ali's Syiqsyiqiyyah sermon with literary criticism analysis method produces two pragmatic approaches, namely: (a) literary criticism that produces aesthetic values, and (b) literary criticism that produces useful values.